Seven spools of thread : a Kwanzaa story - Medearis, Angela Shelf, 1956- (Albert Whitman, 2000)
When they are given the seemingly impossible task of turning thread into gold, the seven Ashanti brothers put aside their differences, learn to get along, and embody the principles of Kwanzaa. Includes information on Kwanzaa, West African cloth weaving, and instructions for making a belt.